Alexithymia and Affect Intensity of Fine Artists. (23rd December 2013) - Botella, Marion; Zenasni, Franck; Lubart, Todd
Abstract Research on creative artists has examined mainly their personality traits or cognitive abilities. However, it seems important to explore also their emotional traits to complete the profile. This study examines two emotional characteristics: alexithymia and affect intensity. Even if most research suggests that artists are less alexithymic and experience more intensively their emotions, Botella, M., Zenasni, F., and Lubart, T. (Psychology of Aesthetics, Creativity, and the Arts, 5, 251, 2011) observed that art students were as alexithymic as psychology students and more alexithymic than a normative population. The aim of this study was to examine these issues with artists and non‐artists and to compare artists to art students. Results indicate that artists are less alexithymic and present higher affect intensity than non‐artists. Moreover, results show that art students present more difficulties processing their emotions than artists.